The role of microcredit program and micro enterprises in poverty reduction - Atik Purmiyati; Retno Setyowati; Marta Sabila Rakhima (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study analyzes the technical efficiency micro-enterprises in agricultural sector and its determinants. It further investigate the effect of the microcredit program of Kredit Perniagaan Rakyat (KUR) on the efficiency of micro-enterprises in East Java Indonesia hence the poverty reduction. In achieving the aforementioned objectives, three methods are employed namely Data Envelopment Analysis (DEA), Tobit Regression, and Logistic Regression. The estimation results of the Micro Enterprises efficiency using DEA shows that under the assumption of Variable Return to Scale 62 percent of the samples have reached full efficiency. However, under the assumption of Constant Return to Scale, 28 percent of the samples have reached full efficiency.. The factors that influence the efficiency based on tobit regression analysis are profit, asset, credit amount, KUR access, realization tempo, age, labor, and business location. Furthermore, factors affecting poverty status based on logistic regression analysis are income, gender, KUR access, and number of household.